Design of High Precision Image Measurement System for Small Workpiece. Issue 4 (April 2021) - Zhang, Xuelin; Fu, Fengzhi; Fan, JunPeng; Fan, Hua
Abstract: At present, there are many problems in the measurement of small machined parts (size ⩽ 70mm, such as micro circuit board, small non-standard parts, etc.), such as the difficulty and low efficiency of detection, the large data of sizes to be detected, and mainly rely on manual work. A high-precision image measurement system based on machine vision is designed in this paper, and the systematic error and random error of the machine vision measurement system are improved from hardware and software. Experiments show that size measurement of small workpiece with high efficiency and high accuracy can be realized by the system successfully. The measurement accuracy reaches micron level, which fully meets the testing requirements of production line, and has great value of industrialization promotion.